Learning Motivations, Styles and Expectations of Students – a Survey at the University of Debrecen - Gál, Tímea; Popovics, Peter; Árváné Ványi, Georgina (Applied Studies in Agribusiness and Commerce, 2018)
Based on the experience of the authors, today's university students have different learning habits, expectations of learning and knowledge compared to previous generations. This raises the question of how traditional teaching, teaching methods effectively suited to their development. In this study, the authors examined with quantitative method the expectations of bachelor and master students concerning the business education at university. The survey was conducted among university students assessing whether students with different BSc/BA or MSc/MA majors show the willingness to continue their studies, and the authors were interested in their expectations concerning the business higher education. The authors also tried to find answers in the survey how well-prepared the students feel for the offered opportunities by today's market environment, or may prefer proceeding with their studies. Among the issues authors searched what are the most effective ways of learning for them, based on learning style, what motivates them to continue learning. What kind of education form is preferred by them to continue studying? They also respond the need of having theoretical and practical knowledge and the importance of developing practical life skills. In addition, it has also been surveyed what other expectations the students have in continuing their studies with regard to the institutions. The authors of this paper are working as team coaches at the Team Academy Debrecen. In the last six years, they worked with numerous teams and have experiences in developing students' skills in teams.JEL Classification: A22